Collaborative knowledge mobilisation to increase awareness and use of new SNOMED clinical terms for fetal alcohol spectrum disorder in England - James T. I. Parsonage; Amy Dillon; Louise Millington; Raja A. S. Mukherjee; Sandra Ionno Butcher; Andy Boyd; Patricia D. Jackson; Cheryl McQuire (Frontiers in Public Health, 2026)
Introduction Fetal alcohol spectrum disorder (FASD) affects an estimated 1.8–3.6% of UK school children and up to 27% of children in care. FASD remains vastly under-diagnosed and under-recorded in UK electronic patient records (EPRs), leading to significant challenges for individuals with the condition. In 2024, we developed new SNOMED clinical terms aligned to UK national guidelines and quality standards for FASD. Aims Through collaborative knowledge mobilisation (KM), we aimed to: i) raise awareness of the importance of utilising these new clinical terms; ii) identify barriers to FASD code usage in primary care EPRs; iii) co-develop creative communication materials and dissemination strategies. Methods We engaged with stakeholders ( N = 18) including paediatricians, general practitioners, wider health professionals, data specialists, third-sector representatives, and researchers, through a workshop and individual meetings. Individuals living with FASD provided their perspectives on the importance of recognising FASD in EPRs, for inclusion in communication materials. Results We co-produced free, publicly available creative communication materials including an animation, infographics and social media images. Materials focus on raising awareness of new SNOMED clinical terms for FASD, address stakeholder reported barriers to clinical coding, and provide actionable recommendations to improve clinical coding for FASD within primary care electronic records, and diagnostic services. We promoted these materials through social media platforms, a press release, conference presentations, and an editorial. Discussion Our collaborative KM work provides an exemplar for developing materials with the aim of supporting improved clinical coding in EPRs. Further work is required to maximise and evaluate the impact of our materials.